Reconsidering policy : complexity, governance and the state - Crowley, Kate; Stewart, Jenny; Kay, Adrian; Head, Brian W. (Policy Press, 2020)
This book reconsiders traditional policy-analytic concepts, and re-develops and extends new ones, in a melded approach defined as systemic institutionalism. This links policy with governance and the state and suggests how real-world issues might be substantively addressed